Comparison of acid exfoliators in carbon nanosheets synthesis from stinging nettle (Urtica dioica) for electrochemical applications - Kanokon Nuilek; Winadda Wongwiriyapan; Vichuda Sattayarut; Andrea Simon; Daniel Koncz-Horvth; Tibor Ferenczi; Ferenc Kristly; Peter Baumli (My University, 2020)
Abstract Carbon nanosheets (CNs) were successfully synthesized from nettle stem (NS) which is an inexpensive material with a high carbon content that is abundantly available in nature. CNs were produced using chemical (potassium hydroxide activation and acid exfoliation) and thermal treatments. Sulfuric (H 2 SO 4 ), phosphoric (H 3 PO 4 ) and nitric (HNO 3 ) acid solutions were used for exfoliation. CNs exfoliated by H 3 PO 4 have higher specific surface area (789 m 2 g −1 ) compared to CNs exfoliated by H 2 SO 4 (705 m 2 g −1 ) and HNO 3 (106 m 2 g −1 ). In this work, NSCNs were found to be a potential candidate for electrode material in electrochemical capacitors. The maximum specific capacitance of the NSCNs exfoliated by H 3 PO 4 is found to be 27.3 F g −1 at a current density of 0.05 A g −1 , while the specific capacitance of NSCNs exfoliated by H 2 SO 4 and HNO 3 is 9.34 F g −1 and 1.71 F g −1 , respectively. Energy density (0.06–0.95 Wh kg −1 ) and power density (20.9–26.7 W kg −1 ) of NSCNs are confirmed to be supercapacitor materials and can be applied in energy storage devices.
Keywords: Urtica dioica; Medicinal plant effects and applications